Desain Pelayanan Pastoral Orang Muda Katolik Gereja Santo Yosafat Surabaya menurut Christus Vivit - Kurniawan, Hilarius Andika; Suwito, Benny (Institutum Ioannis Mariae Vianney Surabayanum, 2024)
Young Catholics are called to continue proclaiming faith in the world as modern-day images of Jesus. In Christus Vivit, Pope Francis identifies young people as the